A TRAINING BY USING GOOGLE MEET FOR ELEMENTARY SCHOOL TEACHERS - Gustiana Gustiana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This Covid outbreak greatly affects the education that supports the 4.0 revolution era by bringing changes in learning in Indonesia. Teachers conduct distance learning (PJJ) through Google Meet as an alternative provided by the principal in improving learning in the classroom. Increasing the teachers’ ability is inseparable from the role of a school principal by providing various trainings that are able to be followed by teachers. This study used the action research method using 2 cycles of enforcement involving 11 teachers. The results of the research showed that the score on the teachers’ ability to make applications was 63 meaning that the level of success was quite good, while in cycle II, the average score increased to 80 with good category. Furthermore, the average score of the teacher's ability to implement google meet in learning in cycle I was 65 with good category and it increased in Cycle II to 80.5 with a good category. Thus, it was concluded that the teacehrs’ ability increased after holding the training.